Descriptive analysis of the unwarranted continuation of antipsychotics for the management of ICU delirium during transitions of care: A multicenter evaluation across New Jersey. (25th April 2021) - Dixit, Deepali; Barbarello Andrews, Liza; Radparvar, Sara; Adams, Christopher; Kumar, Samir T; Cardinale, Maria
Abstract: Purpose: Nearly half of intensive care unit (ICU) patients will develop delirium. Antipsychotics are used routinely for the management of ICU delirium despite limited reliable data supporting this approach. The unwarranted continuation of antipsychotics initiated for ICU delirium is an emerging transitions of care concern, especially considering the adverse event profile of these agents. We sought to evaluate the magnitude of this issue across 6 centers in New Jersey and describe risk factors for continuation. Methods: This multicenter, retrospective study examined adult ICU patients who developed ICU delirium from June 2016 to June 2018. Patients were included in the study if they received at least 3 doses of antipsychotics while in the ICU with presence of either a clinical diagnosis of delirium or a positive Confusion Assessment Method score. Patients were excluded if they were on an antipsychotic before ICU admission. Results: Of the 300 patients included and initiated on antipsychotics for ICU delirium, 157 (52.3%) were continued on therapy upon transfer from the ICU to another level of inpatient care. The number of patients continued on newly initiated antipsychotics further increased to 183 (61%) upon discharge from the hospital. Conclusion: The continuation of antipsychotics for the management of delirium during transitions of care was a common practice across ICUs in New Jersey. Several risk factors for continuation of antipsychotics were identified. Efforts to reduce unnecessary continuation of antipsychotics at transitions of care are warranted.